Demand for Municipal Housing on the State and Local Level – Case Study - Suszyńska, Katarzyna; Muczyński, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of the paper was to estimate the formal level of demand for municipal flats in Poznań, Poland. The volume and structure of the demand were determined in the context of local regulations and criteria of granting housing aid to destitute households. The subject of the study was a population of households who applied for allocation of municipal flat from Poznań city housing stock in the years 2012–2016. The results of the quantitative analysis showed significant discrepancies between real demand for public rental housing and the potential of the city to meet these needs.